Classic Yiddish stories of S.Y. Abramovitsh, Sholem Aleichem, and I.L. Peretz - Wex, Michael, 1954-; Gorelick, Ted; Frieden, Ken, 1955-; Peretz, Isaac Leib, 1851 or 1852-1915; Sholem Aleichem, 1859-1916; Mendele Mokher Sefarim, 1835-1917 (Judaic traditions in literature, music, and art., 2011)
"Two novellas by S.Y. Abramovitsh open this collection of the best short works by three influential nineteenth-century Jewish authors, Abramovitsh's alter ego - Mendele the Book Peddler - introduces himself and narrates both The Little Man and Fishke the Lame. His cast of characters includes Isaac Abraham as tailor's apprentice, choirboy, and corrupt businessman; Mendele's friend Wine 'n' Candles Alter; and Fishke, who travels through the Ukraine with a caravan of beggars." "Sholem Aleichem's lively stories reintroduce us to Tevye, the gregarious dairyman, as he describes the pleasures of raising his independent-minded daughters. These are followed by short monologues in which Aleichem gives voice to unforgettable characters from Eastern Europe to the Lower East Side. Finally, I.L. Peretz's neo-hasidic tales draw on hasidic tradition in the service of modern literature." "These stories provide an unsentimental look back at Jewish life in Eastern Europe. Although.